Parenting, privilege, and pandemic: From surviving to thriving as a mother in the academy. (March 2021) - Beech, Haley H; Sutton, Amber; Cheatham, Leah
As women who have dual roles as parents and academicians, COVID-19 has presented new challenges and opportunities that have impacted our personal and professional lives. This essay provides insight into unique obstacles from the perspective of mothers, researchers, and social workers and challenges the traditional models of work/life balance as professionals in academics. This reflexive essay provides the narratives and experiences of one assistant professor and two doctoral students who are learning to navigate motherhood and professional responsibilities amidst a global pandemic. The prologue presents a perspective from a current assistant professor and her lived experiences followed by the reflections of two doctoral students on how to navigate the academy as mothers and as women. In addition to our personal stories and narratives, we hope to challenge, inspire, and reimagine how our dual roles can be viewed as an asset, rather than a weakness and encourage others in the academy to rise and support women.